Kebijakan Pemerintah Desa Dalam Mempersiapkan Produk Unggulan Wilayah Pedesaan Melalui Optimalisasi Pemanfaatan Pekarangan Rumah - Haryono Haryono (Universitas Muhammadiyah Sidoarjo, 2018)
The aim of this study is following 1) to know the planning of the government policy of village; 2) to understand participation of Jabaran’s societies in utilizing their yard; 3) to find out the potential of the yard to support Jabaran’s excellent products. The type of this study is qualitative descriptive by doing observation and interview deeply to some key for getting data. And the secondary data provided by the local government of or official publications of regency. The result of this study said that 1) the planning of local government policy of to build the village related to UU No 6/2016 about village; 2) Participation of Jabaran’s societies to exploit their yard to produce bordered plants and , and the real steps of the government of collaborate to the university to cultivate ; 3) many yards that have not been utilized whereas they have potential and strategic location passed through river and road of Surabaya-Yogyakarta.